Influence of inulin rich carbohydrates from Jerusalem artichoke (Helianthus tuberosus L.) tubers on probiotic properties of Lactobacillus strains. (March 2019) - Iraporda, Carolina; Rubel, Irene A.; Manrique, Guillermo D.; Abraham, Analía G.
Abstract: The effect of inulin extracted from Jerusalem artichoke ( Helianthus tuberosus L.) tubers on the growth and probiotic properties of different Lactobacillus strains was analyzed. It was demonstrated that L. paracasei BGP1 and L. plantarum CIDCA8327 strains were able to ferment inulin form Jerusalem artichoke tubers. The survival after simulated gastrointestinal conditions was improved in presence of inulin meanwhile the adhesion to intestinal epithelial cells capacity resulted strain- and inulin dose-dependent. Thus, the observed characteristics confer a potential application of this inulin rich carbohydrates extract as an ingredient that not only improves bacterial growth but also enhance its resistance to gastrointestinal conditions. These preliminary results regarding the probiotic-prebiotic interaction indicate that although inulin improved survival of the strains analyzed, the effect on adhesion ability depends on the probiotic studied. Highlights: L. paracasei BGP1 and L. plantarum CIDCA8327 were able to ferment inulin in vitro . Inulin improved probiotic survival after gastrointestinal simulated treatment. Inulin affect probiotic adhesion to intestinal epithelial cells in vitro . Jerusalem artichoke inulin could replace the analogous commercial ingredient.